2023
DOI: 10.12659/msm.938835
|View full text |Cite
|
Sign up to set email alerts
|

Necessity and Importance of Developing AI in Anesthesia from the Perspective of Clinical Safety and Information Security

Abstract: The rapid development of artificial intelligence (AI) technology is due to the significant progress in big data, databases, algorithms, and computing power, and medical research is a vital application direction of AI. The integrated development of AI and medicine has improved medical technology, and the efficiency of medical services and equipment has enabled doctors to better serve patients. The tasks and characteristics of the anesthesia discipline also make AI necessary for its development, and AI has also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 76 publications
0
17
0
Order By: Relevance
“…However, beyond these foundational aspects, a tantalizing prospect emerges as AI assimilates and scrutinizes historical patient data, encompassing anesthesia or procedural sedation history, and delves into pathophysiological information. This not only holds the promise of enhancing anesthesia medicine but also positions AI to play a pivotal role in advancing precision medicine to the forefront of postoperative pain management [ 43 , 44 ].…”
Section: Reviewmentioning
confidence: 99%
“…However, beyond these foundational aspects, a tantalizing prospect emerges as AI assimilates and scrutinizes historical patient data, encompassing anesthesia or procedural sedation history, and delves into pathophysiological information. This not only holds the promise of enhancing anesthesia medicine but also positions AI to play a pivotal role in advancing precision medicine to the forefront of postoperative pain management [ 43 , 44 ].…”
Section: Reviewmentioning
confidence: 99%
“…The development of artificial intelligence in all aspects of anesthesia has brought significant benefits, including airway management, ultrasound-guided interventions, intelligent drug infusion systems, accurate intraoperative monitoring, and perioperative risk assessment ( 120 ). A randomized trial evaluating the performance of an automated inspired oxygen concentration (FiO2 closed-loop system) using a narrower SpO2 target range found that the time spent within the clinically determined alarm limit (86–94%) was as good as with two wider target ranges ( 121 ).…”
Section: The Role Of Artificial Intelligence (Ai) and Machine Learnin...mentioning
confidence: 99%
“…These models enhance the interpretation of EEG signals, facilitating nuanced analyzes of complex data streams for depth of anesthesia (DoA) monitoring. Studies have highlighted the efficacy of direct EEG signal analysis through AI and spectral analysis ( 120 ). Park et al ( 145 ) developed a DoA system utilizing real-time EEG and deep neural network algorithms that surpass traditional bispectral index (BIS) systems in performance.…”
Section: Artificial Intelligence and Real-time Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 10 ] Thus, mastering AI for anticipation and planning in airway management has the potential to surpass the traditional methods of airway management. [ 11 ]…”
Section: Concept Of Aimentioning
confidence: 99%